An Analysis upon Various Developments in Lok Adalat System in India: Present Scenario: Exploring the Role of Lok Adalats in the Indian Legal System (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Lok Adalat is a part of legal aid Schemes and the most convenient alternative which supplements the existing system. Lok Adalat means a 'People’s Court1. However a Lok Adalat is not a Court in its existing connotation,, It is a forum where voluntary efforts aimed at bringing about sett¬lement of disputes between the parties are made through Co¬nciliation and persuation. These are not formal Courts as th¬ey are organized by the legal aid Committees with the support of the local bar, prominent Citizens, social activists and retired of existing judicial officers. Cases are decided by consent and therefore* there is no scope for Challenge against the decision taken. Tension arising out of litigation is totally reduced and cordiality is restored.There was initial resistance to Lok Adalats in some parts of India. The resistance is fast dying cut and now Lok Adalats are welcomed by most of the people. They can easily provide a supplementing method for reducing the number of penning cases.